Sex-specific differences in the distal versus proximal presenting location of acute deep vein thrombosis. Issue 172 (December 2018) - Trinchero, Alice; Scheres, Luuk J.J.; Prochaska, Jürgen H.; Ambaglio, Chiara; Wild, Philipp S.; Middeldorp, Saskia; Konstantinides, Stavros V.; Barco, Stefano
Abstract: Background and aims: Women present with pulmonary embolism (PE) more often than men, while the opposite is true for proximal deep vein thrombosis (DVT). We investigated whether sex-specific differences exist in the presenting location of acute symptomatic DVT among patients without concomitant PE. Methods: We tested our hypothesis in a meta-analysis of studies selected by systematically reviewing PubMed, Embase, and the grey literature. Thereafter, we analysed data of a single-center cohort including patients with first isolated acute DVT to assess the additional impact of age and provoking risk factors on the presenting location of DVT. Results: We identified 7 studies for a total of 20, 534 patients. The weighed pooled absolute difference in the proportion of distal DVT between women and men was +5.4% (95%CI: +0.7%; +9.5%), which corresponds to a pooled odds ratio (OR) of 1.30 (95%CI: 1.07–1.58). This difference was +6.5% (95%CI: +2.1%; +10.9%) for first distal DVT (OR 1.38; 95%CI: 1.11–1.72) and +5.3% (95%CI: +0.5%; +10.0%) for either first or recurrent distal DVT (OR 1.29; 95%CI: 1.03–1.61). In the cohort study, the larger difference in the proportion of distal DVT between women and men was observed among patients aged 51–70 (+9.5%; 95CI: +2.8%; +16.0% compared to those aged 18–50) or with unprovoked events (+8.5%; 95CI: −0.9%; +17.9%). Conclusions: Among patients with first symptomatic isolated acute DVT, women presented with distal DVT more often than men, whereas men had a higher proportion of proximal DVT events. This pattern appeared to depend on age and the absence of provoking risk factors for VTE. Highlights: The proportions of pulmonary embolism versus proximal deep vein thrombosis (DVT) events differ between sexes. We investigated whether the distal versus proximal presenting location of isolated DVT is influenced by sex. Women presented with distal DVT more often than men, whereas men had more often proximal DVT. This pattern appeared to depend on age and the absence of provoking risk factors, but further studies are warranted.